Zirconium-loaded MER type molecular sieve as well as preparation method and application thereof

By mixing fly ash with potassium hydroxide and ZrOCl2, MER-type molecular sieve loaded with zirconium elements was prepared, which solved the problem of fly ash utilization, achieved efficient and low-cost adsorbent preparation, and had good adsorption performance and production. sex.

CN119186489APending Publication Date: 2024-12-27INNER MONGOLIA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411699164.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently utilize fly ash and prepare MER type molecular sieves with strong adsorption capacity with strong adsorption capacity with high adsorption capacity and difficult to achieve mass production.

Method used

By mixing fly ash with potassium hydroxide solution and stirring, then mixing with ZrOCl2 and grinding in water, electrostatic action promotes the entry of zirconium ions into the pores of the molecules, forming a MER-type molecular sieve loaded with zirconium elements, achieving low cost and low energy of the molecular sieve Consumable preparation.

Benefits of technology

The prepared MER-type molecular sieve has a stable lattice structure, a large specific surface area and a uniform pore size. It can effectively adsorb phosphate ions in wastewater, with a removal rate of 99.65%, and can achieve mass production, simplifying the preparation process and avoiding High temperature calcination and addition of molecular sieve seed crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186489A_ABST
    Figure CN119186489A_ABST
Patent Text Reader

Abstract

The invention discloses a zirconium-loaded MER type molecular sieve as well as a preparation method and application thereof, and belongs to the technical field of molecular sieve preparation. Fly ash is used as a raw material, the MER type molecular sieve is obtained after the fly ash and a potassium hydroxide solution are subjected to a high-temperature hydrothermal reaction, the specific surface area of the MER type molecular sieve reaches 22.2079 m < 2 > / g, and the pore diameter is about 10.7306 nm; then mixing and grinding the MER type molecular sieve and a ZrOCl2 solid phase, dissolving the mixed powder in water, stirring for 22-24 hours at 55-65 DEG C to obtain a suspension, and then centrifuging, washing and drying the suspension to obtain the ZrOCl2 / MER type molecular sieve, the removal rate of the zirconium-loaded MER type molecular sieve on phosphate in sewage is as high as 99.65%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieve preparation, and in particular relates to a zirconium-loaded MER type molecular sieve and a preparation method and application thereof. Background Art

[0002] Fly ash is a complex multiphase solid waste left over after coal is burned in a boiler. Fly ash contains not only silicides, iron compounds and aluminum compounds, but also small amounts of elements such as boron, magnesium, calcium, sodium, phosphorus and potassium. As the country gradually standardizes and institutionalizes air pollution control, the dust removal, desulfurization and denitrification technologies of thermal power plants have become increasingly mature, and the output of fly ash has also increased accordingly.

[0003] Fly ash cannot achieve good environmental protection, so the efficient development and utilization of fly ash is of great significance. The chemical composition of fly ash is similar to that of zeolite molecular sieves. Fly ash has porous properties and a large specific surface area. Modification can enhance its adsorption performance. Using the silicon and aluminum rich in fly ash to synthesize molecular sieves with high cost performance and high utilization rate is considered to be one of the effective methods for high-value application of fly ash. In recent years, with the in-depth research on molecular sieve adsorption technology, a variety of new molecular sieve materials and modification methods have been developed, making molecular sieves more widely used and developed. Therefore, if fly ash can be used in large quantities, it can be prepared into a usable molecular sieve carrier and the molecular sieve carrier can be modified, which will become a good way to solve environmental problems, and can also obtain good economic and social benefits. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a zirconium-loaded MER molecular sieve and a preparation method and application thereof, which solve the technical problems of how to efficiently utilize fly ash and how to prepare a zirconium-loaded MER molecular sieve with strong adsorption capacity at low cost and low energy consumption.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is to provide a method for preparing a zirconium-loaded MER molecular sieve from fly ash, which comprises the following steps: S1: Fly ash and potassium hydroxide solution are mixed, the mixture is stirred at 170-180°C for 15-17h, and then the solid-liquid separation is performed to collect the solid product; S2: Wash and dry the solid product to obtain a MER type molecular sieve; the drying temperature is 110-130°C and the drying time is 3.5-4.5h; S3: Mix and grind the MER molecular sieve and ZrOCl2, then dissolve the mixed powder in water and stir at 55-65°C for 22-24h to obtain a suspension; S4: Centrifuge, wash and dry the suspension.

[0006] Furthermore, the concentration of the potassium hydroxide solution is 2-5 mol / L.

[0007] Furthermore, the mass ratio of fly ash to potassium hydroxide in the mixture is 1:0.27~0.67.

[0008] Furthermore, in step S1, the stirring speed is 280-320 rpm.

[0009] Furthermore, in step S1, the reaction temperature is 175° C. and the reaction time is 16 h; in step S2, the drying temperature is 120° C. and the drying time is 4 h.

[0010] Furthermore, the mass ratio of the MER molecular sieve and ZrOCl2 in the mixed powder of step S3 is 1 g: 17.8-125 mg; and the concentration of ZrOCl2 in the suspension is 0.001-0.007 mol / L.

[0011] Furthermore, in step S4, the centrifugal speed is 5000-6000 rpm, and the centrifugal time is 5-6 minutes; washing is washing with water until the washed water does not contain chloride ions; in step S4, the drying temperature is 75-85° C.; and the drying time is 11-12 hours.

[0012] The invention also discloses a zirconium-loaded MER type molecular sieve prepared by the preparation method.

[0013] The invention also discloses the use of the MER type molecular sieve loaded with zirconium element in the preparation of catalyst or adsorbent Furthermore, the adsorbent is used to adsorb phosphate ions in the wastewater, the solid-liquid ratio of the MER molecular sieve loaded with zirconium element in the adsorbent to the wastewater is 1g:10~1000mL, the pH value of the wastewater is 2~8, the adsorption temperature is 20~80℃, and the adsorption time is 180~240min.

[0014] The beneficial effects of the present invention are: 1. The present invention first uses fly ash as raw material to prepare MER type molecular sieve. Compared with other methods for preparing molecular sieves, the preparation method of the present invention is simple, does not require aging operation, does not require the addition of molecular sieve seeds, does not require high-temperature calcination treatment, and the output is greater than laboratory reagent synthesis, and mass production can be achieved.

[0015] 2. Fly ash is widely available and inexpensive. The MER type molecular sieve prepared from it has a stable lattice structure, a large specific surface area, a large pore size and a uniform distribution.

[0016] 3. The MER type molecular sieve prepared in the present invention contains potassium ions, and then the MER type molecular sieve and ZrOCl2 are ground by solid phase mixing to promote the full mixing of the MER type molecular sieve and ZrOCl2, and then the mixed powder is stirred in water, and the electrostatic effect is used to promote the zirconium ions to enter the pores of the molecules, which helps the potassium ions and zirconium ions to undergo a replacement reaction, and finally the zirconium ion content in the molecular sieve is 2.5-3wt%, and the potassium ion content is 6-7wt%; when the molecular sieve is used to adsorb phosphate ions in wastewater, the zirconium ions are positively charged and form a stable chemical bond with phosphate, thereby adsorbing phosphate ions, and the removal rate of phosphate ions in the wastewater can reach 99.65%. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the XRD pattern of the MER type molecular sieve prepared in Example 1; Figure 2 is the XRD pattern of the molecular sieve prepared in Comparative Example 1; Figure 3 XRD patterns of samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3; Figure 4 is a SEM image of the MER type molecular sieve prepared in Example 1; Figure 5 This is the EDS spectrum of the MER type molecular sieve prepared in Example 1; Figure 6 is the Fourier infrared spectrum of the MER type molecular sieve prepared in Example 1; Figure 7 The Fourier transform infrared spectra of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown; Figure 8 This is the full XPS spectrum of the MER type molecular sieve prepared in Example 1; Fig. 9 This is the XPS graph of the O element in the MER type molecular sieve prepared in Example 1; Fig.10 N2 adsorption-desorption isotherm and pore size distribution diagram of the MER type molecular sieve prepared in Example 1; Fig.11 This is the kinetic curve of the adsorption of phosphate ions by the zirconium-loaded MER molecular sieve prepared in Example 1; Fig.12 This is the diffusion model of the adsorption diagram of phosphate ions by the zirconium-loaded MER molecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0018] The raw materials used in the present invention are: fly ash from Jinqiao Thermal Power Plant in Hohhot; potassium hydroxide (KOH, analytical grade AR, 85-90%).

[0019] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0020] Example 1 A zirconium-loaded MER molecular sieve is prepared by the following steps: S1: Weigh 43.2g of potassium hydroxide and dissolve it in water to prepare a 2mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution to a 1L electric lifting mechanical stirring reactor, and then stir and react at 175°C for 16h at a stirring speed of 320rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven to dry for 4 hours at a drying temperature of 120° C. to obtain a MER type molecular sieve.

[0021] S3: Take 1 g of MER molecular sieve and 125 mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100 mL of water and stir at 60 °C for 23 h to obtain a suspension; S4: The suspension is centrifuged at a speed of 6000 rpm for 5 minutes, and the solid is washed with water until the water after washing contains no chloride ions as detected by silver nitrate, and then dried at 80°C for 11 hours to obtain the solid.

[0022] Example 2 A zirconium-loaded MER molecular sieve is prepared by the following steps: S1: Weigh 67.72g of potassium hydroxide and dissolve it in water to prepare a 5mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution into a 1L electric lifting mechanical stirring reactor, and then stir the reaction at 170°C for 16h with a stirring speed of 300rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven for drying for 4.5 hours at a drying temperature of 130° C. to obtain a MER type molecular sieve.

[0023] S3: Take 1 g of MER molecular sieve and 54 mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100 mL of water and stir at 55 °C for 22 h to obtain a suspension; S4: The suspension is centrifuged at a speed of 5000 rpm for 6 minutes, and the solid is washed with water until the water after washing does not contain chloride ions as detected by silver nitrate, and then dried at 75°C for 12 hours to obtain the solid.

[0024] Example 3 A zirconium-loaded MER molecular sieve is prepared by the following steps: S1: Weigh 107.2g potassium hydroxide and dissolve it in water to prepare a 3mol / L potassium hydroxide aqueous solution; add 160g fly ash and the prepared potassium hydroxide aqueous solution to a 1L electric lifting mechanical stirring reactor, and then stir the reaction at 180°C for 17h at a stirring speed of 280rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven for drying for 3.5 hours at a drying temperature of 110° C. to obtain a MER type molecular sieve.

[0025] S3: Take 1 g of MER molecular sieve and 17.8 mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100 mL of water and stir at 60 °C for 23 h to obtain a suspension; S4: The suspension is centrifuged at a speed of 6000 rpm for 6 minutes, and the solid is washed with water until the water after washing does not contain chloride ions as detected by silver nitrate, and then dried at 85°C for 11 hours to obtain the solid.

[0026] Example 4 A zirconium-loaded MER molecular sieve is prepared by the following steps: S1: Weigh 89.6g of potassium hydroxide and dissolve it in water to prepare a 2mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution into a 1L electric lifting mechanical stirring reactor, and then stir and react at 175°C for 15h with a stirring speed of 300rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven to dry for 4 hours at a drying temperature of 120° C. to obtain a MER type molecular sieve.

[0027] S3: Take 1 g of MER molecular sieve and 100 mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100 mL of water and stir at 65 °C for 24 h to obtain a suspension; S4: The suspension is centrifuged at a speed of 5500 rpm for 6 minutes, and the solid is washed with water until the water after washing contains no chloride ions as detected by silver nitrate, and then dried at 75°C for 12 hours to obtain the solid.

[0028] Comparative Example 1 A molecular sieve is prepared by the following steps: S1: Weigh 67.72g of potassium hydroxide and dissolve it in water to prepare a 2mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution into a 1L electric lifting mechanical stirring reactor, and then stir the reaction at 175°C for 12h with a stirring speed of 300rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven to dry for 4 hours at a drying temperature of 120°C.

[0029] Comparative Example 2 A molecular sieve is prepared by the following steps: S1: Weigh 43.2g of potassium hydroxide and dissolve it in water to prepare a 2mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution to a 1L electric lifting mechanical stirring reactor, and then stir and react at 175°C for 16h at a stirring speed of 320rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven to dry for 4 hours at a drying temperature of 120° C. to obtain a MER type molecular sieve.

[0030] S3: Take 1 g of MER molecular sieve and 250 mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100 mL of water and stir at 60 °C for 23 h to obtain a suspension; S4: The suspension is centrifuged at a speed of 6000 rpm for 5 minutes, and the solid is washed with water until the water after washing contains no chloride ions as detected by silver nitrate, and then dried at 80°C for 11 hours to obtain the solid.

[0031] Comparative Example 3 A molecular sieve is prepared by the following steps: S1: Weigh 43.2g of potassium hydroxide and dissolve it in water to prepare a 2mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution to a 1L electric lifting mechanical stirring reactor, and then stir and react at 175°C for 16h at a stirring speed of 320rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven to dry for 4 hours at a drying temperature of 120° C. to obtain a MER type molecular sieve.

[0032] S3: Take 1 g of MER molecular sieve and 534 mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100 mL of water and stir at 60 °C for 23 h to obtain a suspension; S4: The suspension is centrifuged at a speed of 6000 rpm for 5 minutes, and the solid is washed with water until the water after washing contains no chloride ions as detected by silver nitrate, and then dried at 80°C for 11 hours to obtain the solid.

[0033] Comparative Example 4 A molecular sieve is prepared by the following steps: S1: Weigh 96g of potassium hydroxide and dissolve it in water to prepare a 5mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution to a 1L electric lifting mechanical stirring reactor, and then stir the reaction at 180°C for 15h at a stirring speed of 320rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven for drying for 3.5 hours at a drying temperature of 110° C. to obtain a MER type molecular sieve.

[0034] S3: Take 1 g of MER molecular sieve and 178 mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100 mL of water and stir at 65 °C for 22 h to obtain a suspension; S4: The suspension is centrifuged at a speed of 6000 rpm for 6 minutes, and the solid is washed with water until the water after washing does not contain chloride ions as detected by silver nitrate, and then dried at 85°C for 11 hours to obtain the solid.

[0035] Comparative Example 5 A molecular sieve is prepared by the following steps: S1: Weigh 43.2g of potassium hydroxide and dissolve it in water to prepare a 2mol / L potassium hydroxide aqueous solution; add 160g of fly ash and the prepared potassium hydroxide aqueous solution to a 1L electric lifting mechanical stirring reactor, and then stir and react at 175°C for 16h at a stirring speed of 320rpm. After the reaction is completed, filter and collect the solid product; S2: Wash the solid product with deionized water until the pH of the solid product is neutral, and then put it into an oven to dry for 4 hours at a drying temperature of 120° C. to obtain a MER type molecular sieve.

[0036] S3: Take 1g of MER molecular sieve and 125mg of ZrOCl2 in a mortar, mix and grind, then dissolve the mixed powder in 100mL of water, add 5mL of 25wt% ammonia water, and stir at 60℃ for 23h to obtain a suspension; S4: The suspension is centrifuged at a speed of 6000 rpm for 5 minutes, and the solid is washed with water until the water after washing contains no chloride ions as detected by silver nitrate, and then dried at 80°C for 11 hours to obtain the solid.

[0037] Experimental example The MER molecular sieves prepared in the six embodiments of the present invention have similar performances. Taking Embodiment 1 as an example, the performance of the related products is described.

[0038] 1. Structural test X-ray diffraction (XRD) analysis was performed on the MER molecular sieve prepared in Example 1 and the molecular sieve prepared in Comparative Example 1 using a PANalytical diffractometer, CuKα1 radiation λ=1.54178Å, the Bragg angle range is 5~80°, and the XRD spectrum is as follows: Figure 1~2 As shown in the XRD spectrum, it can be seen that the MER type molecular sieve prepared in Example 1 exhibits the same 10.32 (Si 22.7 Al 10.3 O 64 )(H2O) 24.32 (JCPDS86-1110) corresponding single crystal phase, unit cell constant a = 14.0948 (6), b = 14.2026 (6), c = 10.0421 (5), orthorhombic space group Immm; the highest peak of the sample prepared in comparative example 1 is not at the same position as (JCPDS86-1110), and the comparative sample is affected by the preparation process, its skeleton structure is destroyed, and more skeleton defects are generated. Similarly, the samples prepared in Examples 1 to 3 and Comparative Examples 2 to 3 are subjected to X-ray diffraction analysis, and the XRD patterns are as follows Figure 3 As shown, it can be seen that the characteristic diffraction peak of the comparative sample disappears significantly and turns into an amorphous characteristic diffraction peak, resulting in a change in the crystal structure of the molecular sieve.

[0039] The structure of the MER molecular sieve prepared in Example 1 was observed using a Hitachi S4800 field emission scanning electron microscope. Figure 4 As shown in the figure, it can be seen that the MER type molecular sieve prepared is in the shape of a rectangular rod, and some are in the shape of a thinner sheet. The MER type molecular sieve prepared in Example 1 was analyzed by energy chromatography, and the analysis diagram is shown in FIG. Figure 5 As shown, The functional group analysis of the MER type molecular sieve prepared in Example 1 was performed using a Fourier transform infrared spectrometer (FT-IR). The infrared spectrum is shown in FIG. Figure 6 As shown in the figure, it can be seen that at 3609~3614cm −1 and 3465~3444cm −1 is a molecule with hydrogen bonds, υ(OH); at 1638cm −1 and 1633cm −1 The high-frequency narrow band near 1025 cm-1 can be attributed to the δ(OH) of adsorbed water molecules; −1 and 1031cm −1 The peak at 785-790 cm corresponds to the combined vibrations υ(Si-O-Si) and υ(Si-O-Al); therefore, −1 and 642~640cm −1 The bands in the frequency range are attributed to Al-O-Si stretching; finally, at 439–431 cm −1 The peaks at are attributed to υ(SiO4) and υ(AlO4) tetrahedral rings. The structures of the samples prepared in Examples 1 to 3 and Comparative Examples 2 to 3 were also analyzed using a Fourier transform infrared spectrometer. Figure 7 As shown, at 600~700cm -1 The peaks in the range correspond to the Zr-O-Zr-O four-membered ring vibration of the zirconia cluster, reflecting the interaction between Zr atoms and O atoms; the slight band shift (energy shift from low to higher energy) can confirm that ZrO 2+ The ions were successfully incorporated into the MER molecular sieve structure.

[0040] The X-ray photoelectron spectrum (XPS) of the MER type molecular sieve prepared in Example 1 was measured using a VG Scientific ESCALAB Mark II spectrometer, which is equipped with two ultra-high vacuum (UHV) chambers. The full XPS spectrum of the MER type molecular sieve is shown in FIG. Figure 8 As shown in the full spectrum, it can be seen that the MER type molecular sieve contains Si and Al elements. The XPS spectrum of the O element in the MER type molecular sieve is as follows Fig. 9 As shown, 531 eV and 531.5 eV are Al-O bonds and Si-O bonds, respectively.

[0041] The zirconium-loaded MER molecular sieves prepared in Examples 1 to 3 and Comparative Examples 2 to 5 were subjected to elemental analysis using a high-resolution inductively coupled plasma mass spectrometer. The results of the potassium ion and zirconium ion contents in the samples are shown in Table 1. Table 1

[0042] It can be seen from the table that the zirconium ion content in the MER type molecular sieve loaded with zirconium element in the embodiment is 2.5-3wt%, and the potassium ion concentration is 6-7wt%.

[0043] 2. Adsorption performance test ① The MER molecular sieve prepared in Example 1 was subjected to N2 adsorption-desorption test on the ASAP2020 system. The N2 adsorption-desorption isotherm and pore size distribution obtained in Example 1 are shown in FIG. Fig.10 As shown, it can be seen that it belongs to the type II adsorption isotherm. The gas adsorption isotherm produced by non-porous or macroporous materials presents a reversible type II isotherm; its linear shape reflects unrestricted monolayer-multilayer adsorption; due to the strong interaction between the adsorbate and the surface, the adsorption amount rises rapidly at a lower relative pressure, and the curve is convex; the inflection point of the isotherm usually appears near the monolayer adsorption. As the relative pressure continues to increase, multilayer adsorption gradually forms. When the saturated vapor pressure is reached, the adsorption layer is infinite, and the adsorption has not reached saturation. The thickness of the multilayer adsorption seems to be able to increase indefinitely. According to the classification of the International Union of Pure and Applied Chemistry (IUPAC), its retention loop is judged to be H3 type. The pores reflected by H3 type include flat slit structures, cracks and wedge structures. The H3 type hysteresis loop is given by flaky granular materials or crack pore materials, and no adsorption saturation is shown in the higher relative pressure region, which is consistent with the morphology presented by the SEM image of the MER type molecular sieve. The surface area tested is shown in Table 2.

[0044] Table 2

[0045] ② Prepare 100mL of an aqueous solution with a phosphate ion concentration of 50ppm and a pH value of 5 as simulated wastewater, take 1g of the MER molecular sieve loaded with zirconium element prepared in Examples 1 to 3 and Comparative Examples 2 to 5 respectively in the wastewater, adsorb for 4h at 40°C, record the adsorption time, adsorption amount and solution concentration in detail, and then calculate the removal rate of phosphate ions by the MER molecular sieve loaded with zirconium element according to the concentration of phosphate ions in the wastewater. The calculation results are shown in Table 3. Table 3

[0046] It can be seen from the table that the removal rate of phosphate ions in wastewater by the zirconium-loaded MER molecular sieve in the embodiment can reach 99.65%, while the phase structure of the molecular sieve in the comparative example changes significantly, and the removal capacity of phosphate is significantly reduced.

[0047] According to the experimental data of the adsorption process of the sample in Example 1, the adsorption kinetics curve is drawn, as shown in FIG. Fig.11 As shown in Figure 2, the adsorption kinetics of phosphate ions on molecular sieves belongs to the second-order kinetics (PSO). Fig.12 The adsorption diagram diffusion model of the MER type molecular sieve loaded with zirconium element in Example 1 shows that the adsorption process includes three stages. In the first stage, the slope is the largest, driven by the phosphate concentration difference, and the adsorption rate is controlled by the concentration difference. In the second stage, the phosphate gradually migrates into the pores and is absorbed by the surface under the influence of the Zr@MER molecular sieve pores. The slope increases slowly, indicating that the secondary diffusion of phosphate in Zr@MER controls the adsorption rate. According to the zeta potential, Zr@MER is positively charged, and Zr ions are positively charged, forming stable chemical bonds with phosphates, having a higher binding capacity for phosphates, increasing the adsorption amount, and improving the removal capacity. In the third stage, the slope is gentle, and the adsorption and desorption in the pores reach equilibrium.

[0048] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing a zirconium-loaded MER molecular sieve from fly ash, characterized in that: The following steps are involved: S1: fly ash and potassium hydroxide solution are mixed, the mixture is stirred at 170-180°C for 15-17h, and then the solid-liquid separation is performed to collect the solid product; S2: washing and drying the solid product to obtain a MER type molecular sieve; the drying temperature is 110-130° C., and the drying time is 3.5-4.5 h; S3: Mix and grind the MER molecular sieve and ZrOCl2, then dissolve the mixed powder in water, and stir at 55-65° C. for 22-24 hours to obtain a suspension; S4: centrifuging, washing and drying the suspension to obtain.

2. The method for preparing a zirconium-loaded MER molecular sieve from fly ash according to claim 1, characterized in that: The concentration of the potassium hydroxide solution is 2-5 mol / L.

3. The method for preparing zirconium-loaded MER molecular sieve from fly ash according to claim 1, characterized in that: The mass ratio of fly ash to potassium hydroxide in the mixture is 1:0.27-0.

67.

4. The method for preparing zirconium-loaded MER molecular sieve from fly ash according to claim 1, characterized in that: The stirring speed in step S1 is 280-320 rpm.

5. The method for preparing zirconium-loaded MER molecular sieve from fly ash according to claim 1, characterized in that: In step S1, the reaction temperature is 175° C. and the reaction time is 16 h; in step S2, the drying temperature is 120° C. and the drying time is 4 h.

6. The method for preparing zirconium-loaded MER molecular sieve from fly ash according to claim 1, characterized in that: In step S3, the mass ratio of the MER molecular sieve to ZrOCl2 in the mixed powder is 1 g: 17.8-178 mg; the concentration of ZrOCl2 in the suspension is 0.001-0.007 mol / L.

7. The method for preparing zirconium-loaded MER molecular sieve from fly ash according to claim 1, characterized in that: In step S4, the centrifugal speed is 5000-6000 rpm, and the centrifugal time is 5-6 minutes; washing is washing with water until the washed water does not contain chloride ions; in step S4, the drying temperature is 75-85° C.; and the drying time is 11-12 hours.

8. A zirconium-loaded MER molecular sieve, characterized in that: The method for preparing a zirconium-loaded MER molecular sieve using fly ash as claimed in any one of claims 1 to 7 is adopted to prepare the same.

9. An application of a zirconium-loaded MER molecular sieve, characterized in that: The zirconium-loaded MER molecular sieve according to claim 8 is used to prepare a catalyst or an adsorbent.

10. The use of the zirconium-loaded MER molecular sieve according to claim 9, characterized in that: The adsorbent is used to adsorb phosphate ions in wastewater, the solid-liquid ratio of the MER molecular sieve loaded with zirconium element in the adsorbent to the wastewater is 1g:10-1000mL, the pH value of the wastewater is 2-8, the adsorption temperature is 20-80°C, and the adsorption time is 180-240min.

Citation Information

Patent Citations

  • Water treatment system adopting molecular sieves prepared from flyash of power plants for filtration

    CN102524160A

  • Method for the preparation of zeolitic materials from industrial by-products and other abundant and low-cost raw materials, and their use in the treatment of contaminated aqueous effluents.

    MX2018003805A

  • Catalysts for the reduction of ammonia emission from rich-burn exhaust

    US20140079616A1